Preparation method and application of humic acid-based metal coordination material
Patent Information
- Application Number
- CN202311549734.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-21
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2043-11-21
AI Technical Summary
但是作为负极材料,腐植酸比容量比较低,特别是在高电流下,稳定性较差,尚不能满足高性能锂电池的要求
[0020]1、本发明基于简单的水热反应,制备腐殖酸基金属配位材料,还可通过调控金属离子的种类开发多种HA-金属配位材料,从而得到优异性能的LIBs负极材料,具有十分重要的现实意义,有望成为一种制备高性能LIBs电极的极具潜力策略。
Smart Images

Figure HDA0004559219210000011 
Figure HDA0004559219210000021 
Figure HDA0004559219210000031
Abstract
Description
Technical Field
[0001] This invention belongs to the field of lithium-ion battery anode material technology, specifically relating to a method for preparing and applying a humic acid-based metal coordination material. Background Technology
[0002] Over the past few decades, the demand for high-performance rechargeable lithium-ion batteries (LIBs) has been growing. Currently, the most widely used graphite anode in commercial LIBs has a relatively low theoretical specific capacity (372 mAh g). -1 The graphite electrode's poor rate performance and inability to meet the demand for high-capacity, fast energy storage have prompted researchers to seek more advanced and novel materials to replace it.
[0003] In recent years, research on anode materials has mainly focused on metal oxide / carbon composite electrode materials. These electrode materials have achieved good electrochemical performance to a certain extent, but the preparation process requires high-temperature pyrolysis / carbonization under different atmospheres (such as Ar, N2 and Air), with temperatures generally greater than 800℃. This is not conducive to industrial production, as high-temperature processing will cause huge energy consumption and large amounts of carbon emissions.
[0004] Biomass materials are naturally carbon-neutral, and the formation of biomass itself is a carbon fixation process. Therefore, the development and utilization of biomass materials will not increase carbon dioxide in the atmosphere. These characteristics are particularly in line with the current advocated path of sustainable development. At the same time, the structure of biomass materials itself has high mechanical modulus and abundant polar groups, which can regulate the uniform deposition of lithium ions and inhibit the growth of lithium dendrites.
[0005] Humic acid (HA) is a biomass material widely used due to its renewable, biodegradable, environmentally friendly, and low-cost properties. It is abundant, with large reserves and wide distribution, and can be widely obtained from wood, soil, or coal. This organic material has a basic structure of aromatic and alicyclic rings, and also contains abundant redox active groups, such as carbonyl, carboxyl, and hydroxyl groups, earning it the nickname "natural graphene oxide." It has been proven to possess considerable electrochemical performance and can be directly used as a negative electrode active material in lithium-ion batteries, as reported in the literature. However, as a negative electrode material, humic acid has a relatively low specific capacity, especially at high currents, and exhibits poor stability, thus not yet meeting the requirements of high-performance lithium-ion batteries. Summary of the Invention
[0006] Based on the above-mentioned prior art, the present invention provides a method for preparing humic acid-based metal coordination materials and their application. The present invention prepares humic acid-based metal coordination materials based on a simple hydrothermal reaction, and uses them as active materials for preparing LIBs anodes, exhibiting advantages such as high specific capacity, excellent cycle stability and rate performance.
[0007] The technical solution adopted to achieve the above-mentioned objectives of this invention is as follows:
[0008] A method for preparing a humic acid-based metal coordination material includes the following steps:
[0009] S1. Mix the aqueous solution of metal salt and the aqueous solution of humic acid evenly to obtain a mixed solution;
[0010] S2. The mixed solution is subjected to a hydrothermal reaction. After the reaction is complete, the mixture is centrifuged, washed, and the resulting precipitate is dried to obtain the humic acid-based metal coordination material.
[0011] Furthermore, the metal salt is selected from at least one of water-soluble manganese salts, cobalt salts, nickel salts, iron salts, and copper salts.
[0012] Furthermore, the manganese salt is selected from at least one of manganese chloride, manganese sulfate, and manganese nitrate; the cobalt salt is selected from at least one of cobalt chloride, cobalt sulfate, and cobalt nitrate; the nickel salt is selected from at least one of nickel chloride, nickel sulfate, and nickel nitrate; the iron salt is selected from at least one of ferric chloride, ferric sulfate, and ferric nitrate; and the copper salt is selected from at least one of copper chloride, copper sulfate, and copper nitrate.
[0013] Furthermore, the mass concentration of the metal salt aqueous solution is 1-10%, and the mass concentration of the humic acid aqueous solution is 0.1-1%.
[0014] Furthermore, the mass ratio of the metal salt to humic acid is 1 to 10:1.
[0015] Furthermore, the hydrothermal reaction is carried out at a temperature of 120–190°C for a duration of 12–24 hours.
[0016] Application of a humic acid-based metal coordination material prepared by the above method in lithium-ion batteries.
[0017] Furthermore, the humic acid-based metal coordination material is used as an active material to prepare the negative electrode of a lithium-ion battery. The specific preparation method is as follows:
[0018] The prepared humic acid-based metal coordination material (HA-Mn material), conductive additive acetylene black, and binder polyvinylidene fluoride (PVDF) were added to the dispersion solvent N-methylpyrrolidone (NMP). The mass ratio of HA-Mn material, conductive additive acetylene black, and binder PVDF was 6:3:1 to 8:1:1, and the mass ratio of the above solids added to the dispersion solvent NMP was approximately 1:(6 to 10). Subsequently, the mixture was magnetically stirred (stirring time not less than 12 hours) to disperse it evenly and form an electrode slurry. The electrode slurry was coated onto the surface of a copper foil, vacuum dried at 80-120℃, and finally stamped and cut to form a negative electrode sheet.
[0019] Compared with the prior art, the advantages and beneficial effects of the present invention are as follows:
[0020] 1. This invention prepares humic acid-based metal coordination materials based on a simple hydrothermal reaction. Furthermore, by controlling the types of metal ions, various HA-metal coordination materials can be developed, thereby obtaining LIBs anode materials with excellent performance. This invention has significant practical implications and is expected to become a highly promising strategy for preparing high-performance LIBs electrodes.
[0021] 2. This invention uses humic acid, a biomass material, as a ligand raw material, which has a significant cost advantage and makes the prepared electrode material more environmentally friendly.
[0022] 3. Compared with humic acid and some metal MOF materials, the electrode prepared by the humic acid-based metal coordination material of the present invention has advantages such as higher specific capacity, more stable cycle performance and better rate performance. This provides a way to improve the specific capacity and stability of lithium battery anodes and promotes the development of lithium battery anodes.
[0023] 4. The process of this invention is simple, reliable, green and environmentally friendly. It does not require the use of acids, alkalis and organic reagents, has high yield, does not require high-temperature carbonization, and has mild preparation conditions. It can significantly reduce the cost of battery preparation to a certain extent and can be industrialized and mass-produced. It has important practical significance for promoting the application and development of lithium-ion batteries. Attached Figure Description
[0024] Figure 1 SEM images of the humic acid-based metal coordination materials prepared in Examples 1-2 are shown. Figure 1 (a) is a SEM image of the HA-Mn material prepared in Example 1. Figure 1 (b) is a SEM image of the HA-Co material prepared in Example 2.
[0025] Figure 2 SEM images of the manganese metal-organic framework material prepared for Comparative Example 1 and pure humic acid for Comparative Example 2.
[0026] in, Figure 2 (a) is a SEM image of Mn-MOFs material. Figure 2 (b) is the SEM image of pure HA in Comparative Example 2.
[0027] Figure 3 XRD patterns of the humic acid-based metal coordination materials prepared in Examples 1-2, the manganese metal-organic framework material prepared in Comparative Example 1, and pure humic acid in Comparative Example 2.
[0028] Figure 4Cyclic voltammetry curves are shown for the humic acid-based metal coordination materials prepared in Examples 1-2, the manganese metal-organic framework material prepared in Comparative Example 1, and pure humic acid in Comparative Example 2. Figure 4 (a) shows the CV curve of HA-Mn material. Figure 4 (b) shows the CV curve of the HA-Co material. Figure 4 (c) shows the CV curves of the Mn-MOFs material. Figure 4 (d) is the CV curve of pure HA.
[0029] Figure 5 EIS spectra of the humic acid-based metal coordination materials prepared in Examples 1-2, the manganese metal-organic framework material prepared in Comparative Example 1, and the pure humic acid in Comparative Example 2.
[0030] Figure 6 The graphs show the cycling stability of the humic acid-based metal coordination materials prepared in Examples 1-2, the manganese metal-organic framework material prepared in Comparative Example 1, and the pure humic acid in Comparative Example 2 under low current.
[0031] Figure 7 The stability performance of the materials prepared in Examples 1-2, the Mn-MOFs material prepared in Comparative Example 1, and the HA material prepared in Comparative Example 2 under high current for long-term cycling is shown in the graph.
[0032] Figure 8 Rate performance curves of the materials prepared in Examples 1-2, the Mn-MOFs material prepared in Comparative Example 1, and the HA material prepared in Comparative Example 2 at different current densities. Detailed Implementation
[0033] The present invention will now be described in detail with reference to specific embodiments.
[0034] Example 1
[0035] 1. Dissolve 296 mg of MnCl2 in 10 ml of deionized water to obtain an aqueous solution of MnCl2.
[0036] 2. Dissolve 100 mg of humic acid (purchased from Aladdin Reagent Company, with fulvic acid FA≥90%; product sourced from lignite) in 25 ml of deionized water and sonicate for 40 min to obtain an aqueous solution of humic acid.
[0037] 3. Mix MnCl2 aqueous solution and humic acid aqueous solution, and stir magnetically for 20 min to obtain a mixed solution. Then transfer the mixed solution to a high-pressure reactor, heat to 180℃ for 36 min, and keep at this temperature for 15 h. Then cool naturally to room temperature, transfer the cooled mixed product to a centrifuge tube, centrifuge at 6000 r / min for 10 min, remove the supernatant, add deionized water and centrifuge again. Repeat this operation 3 to 4 times. Transfer the obtained precipitate to a vacuum drying oven and maintain at 80℃ and 1 Pa vacuum for 24 h to obtain the humic acid-based manganese metal coordination material, abbreviated as HA-Mn material.
[0038] Comparative Example 1
[0039] 1. Dissolve 296 mg of MnCl2·4H2O in 10 ml of deionized water to obtain an aqueous solution of MnCl2.
[0040] 2. Add 100 mg of 4,4'-biphenyldicarboxylic acid (BPDC) to 25 ml of deionized water, and add about 32 mg of NaOH while stirring to completely dissolve it, so as to obtain an aqueous solution of 4,4'-biphenyldicarboxylic acid.
[0041] 3. Mix MnCl2 aqueous solution and 4,4'-biphenyl dicarboxylic acid aqueous solution, and stir magnetically for 20 min to obtain a mixed solution. Then transfer the mixed solution to a high-pressure reactor, heat to 180℃ for 36 min, and keep at this temperature for 15 h. After the reaction is complete, cool to room temperature, transfer the cooled mixed product to a centrifuge tube, centrifuge at 6000 r / min for 10 min, discard the supernatant, add deionized water and centrifuge again. Repeat this operation 3 to 4 times. Transfer the obtained precipitate to a vacuum drying oven and maintain at 80℃ and 1 Pa vacuum for 24 h to obtain manganese metal-organic framework material, abbreviated as Mn-MOF material.
[0042] Comparative Example 2
[0043] Humic acid raw materials are ground to obtain humic acid powder.
[0044] Example 2
[0045] 1. Dissolve 435 mg of Co(NO3)2·6H2O in 10 ml of deionized water to obtain an aqueous solution of Co(NO3)2.
[0046] 2. Dissolve 100 mg of humic acid in 25 ml of deionized water and sonicate for 40 min to obtain an aqueous solution of humic acid.
[0047] 3. Mix Co(NO3)2 aqueous solution and humic acid aqueous solution, and stir magnetically for 20 min to obtain a mixed solution. Transfer the mixed solution to a high-pressure reactor, heat to 180℃ for 36 min, and keep at this temperature for 15 h. After the reaction is complete, let it cool naturally to room temperature. Transfer the cooled mixed product to a centrifuge tube and centrifuge at 6000 r / min for 10 min. Remove the supernatant, add deionized water and centrifuge again. Repeat this operation 3 to 4 times. Transfer the obtained precipitate to a vacuum drying oven and maintain it at 80℃ and 1 Pa vacuum for 24 h to obtain the humic acid-based cobalt coordination material, abbreviated as HA-Co material.
[0048] The humic acid-based metal coordination materials prepared in Examples 1-2, the manganese metal-organic framework material prepared in Comparative Example 1, and the pure humic acid in Comparative Example 2 were scanned using a scanning electron microscope. The SEM images of the humic acid-based metal coordination materials prepared in Examples 1-2 are shown below. Figure 1 As shown, SEM images of the manganese metal-organic framework material prepared in Comparative Example 1 and the pure humic acid in Comparative Example 2 are as follows. Figure 2 As shown. Comparison Figure 1 and Figure 2 It can be seen that the humic acid-based metal coordination materials prepared in Examples 1-2 exhibit a fluffy, porous, snowball-like structure, while the manganese metal-organic framework material prepared in Comparative Example 1 has a fragmented structure, and the pure humic acid in Comparative Example 2 has an amorphous bulk structure. Compared to the fragmented structure of the manganese metal-organic framework material in Comparative Example 1 and the amorphous bulk structure of the humic acid in Comparative Example 2, the humic acid-based metal coordination materials in Examples 1-2 have a larger specific surface area and more pores. This porous structure can effectively alleviate the volume expansion of the electrode material during charging and discharging, and can also expose more active sites and more lithium-ion transport channels, thereby obtaining additional storage capacity, greatly improving its cycle stability, and bringing excellent cycle performance and rate performance.
[0049] The humic acid-based metal coordination materials prepared in Examples 1-2 and Comparative Examples 1-2 were subjected to X-ray diffraction (XRD) analysis. The obtained XRD patterns are shown below. Figure 3 As shown, by Figure 3 It can be seen that the humic acid-based metal coordination materials prepared in Examples 1-2 have similar amorphous spectral peaks to the pure humic acid in Comparative Example 2, indicating that the chelated humic acid-based metal coordination materials still exhibit the same amorphous characteristics as humic acid. In contrast, the Mn-MOFs material prepared in Comparative Example 1 has typical crystalline peaks, indicating that the materials prepared in Examples 1-2 are amorphous humic acid-based metal salt compounds different from MOFs.
[0050] Cyclic voltammetry tests were performed on the humic acid-based metal coordination materials prepared in Examples 1-2, the manganese metal-organic framework material prepared in Comparative Example 1, and pure humic acid in Comparative Example 2. The scan rate was 0.2 mV s⁻¹, the voltage range was 0–3 V, and the test temperature was 30 °C. The obtained cyclic voltammetry curves are shown below. Figure 4 As shown. Comparison Figure 4 It can be observed that the CV spectra of the manganese metal-organic framework materials prepared in Examples 1-2 have a larger area, indicating that the chelation of HA with metal ions results in higher redox activity. The significant difference in curves between the first and subsequent scan cycles originates from the formation of the SEI film, the decomposition of the electrolyte, and the occurrence of irreversible reactions. Meanwhile, the humic acid-based metal coordination materials prepared in Examples 1-2 did not show significant (or negligible) shifts in their redox peaks during repeated scan cycles, while the oxidation and reduction peak potentials of pure HA continuously changed. This indicates that the manganese metal-organic framework materials of this invention have better stability and reversibility compared to the pure HA electrode. The CV spectra of the HA-Mn material prepared in Example 1 are shown below. Figure 4 (a) and the CV spectrum of the Mn-MOFs material prepared in Comparative Example 1 ( Figure 4 (c) Comparison shows that HA-Mn has better cycle stability and reversibility compared to Mn-MOFs materials.
[0051] The humic acid-based metal coordination materials prepared in Examples 1-2, the manganese metal-organic framework material prepared in Comparative Example 1, and the pure humic acid in Comparative Example 2 were subjected to electrochemical impedance spectroscopy (EIS) tests. The obtained EIS spectra are shown below. Figure 5 As shown, by Figure 5 It can be seen that all EIS plots consist of a semicircle in the high-frequency region and a sloping line in the low-frequency region, which are related to the charge transfer resistance (Rct) and the diffusion resistance of Li+ ions, respectively. Obviously, HA-Mn and HA-Co materials show smaller Rct and steeper slopes in the low-frequency region, indicating that the humic acid-based metal coordination material of the present invention has better conductivity and ion diffusion efficiency.
[0052] The humic acid-based metal coordination materials prepared in Examples 1-2, the manganese metal-organic framework material prepared in Comparative Example 1, and the pure humic acid in Comparative Example 2 were subjected to cycling stability tests under low current (90 cycles, 0.1 Ag). -1 Under the condition that the voltage range is 0-3V, the obtained cycle stability performance diagram is shown below. Figure 6 As shown. By Figure 6 As can be seen, the HA-Mn material prepared in Example 1 exhibits the highest specific capacity and the best stability. After activation by introducing metal ions, the specific capacity reaches as high as 1006.6 mAh g after 35 cycles. -1It remained stable thereafter, with a decrease in specific capacity only occurring after 90 cycles, after which the specific capacity remained at 1024.1 mAh g⁻¹. -1 In contrast, the Mn-MOFs material in Comparative Example 1 exhibited a specific capacity of only 189 mAh g after 90 cycles. -1 The HA-Co material prepared in Example 2 had an initial discharge specific capacity of 1496 mAh g. -1 After 90 cycles, its specific capacity remained at 815.1 mAh g. -1 The initial discharge specific capacity of the pure HA material in Comparative Example 2 was only 152.4 mAh g. -1 After 90 cycles, its specific capacity remained at only 287.4 mAh g. -1 The results show that by introducing metal ions, the redox activity of HA materials can be effectively improved, and their charge-discharge specific capacity can be increased. At the same time, the fluffy and porous snowball-like morphology gives it a larger specific surface area and a richer pore structure, which is conducive to the rapid movement and insertion / extraction of lithium ions in the electrode, stabilizes the electrode structure, and thus obtains better electrochemical performance.
[0053] The humic acid-based metal coordination materials prepared in Examples 1-2, the manganese metal-organic framework material prepared in Comparative Example 1, and the pure humic acid in Comparative Example 2 were subjected to long-term cycling stability tests (500 cycles, 1 Ag) under high current. -1 Under the condition of a voltage range of 0–3V, the obtained long-term cycling stability performance graph is shown below. Figure 7 As shown. By Figure 7 It can be seen that the HA-Mn material of Example 1 and the HA-Co material prepared in Example 2 exhibit good specific capacity and stability. After 500 cycles, the specific capacity of the HA-Mn material of Example 1 remained at 351.7 mAh g⁻¹. -1 The specific capacity of the HA-Co material in Example 2 remained at 436.4 mAh g. -1 The specific capacity of the Mn-MOFs material in Comparative Example 1 was only 229 mAh g. -1 The specific capacity of Comparative Example 2 was only 141.1 mAh g. -1 This indicates that the introduction of metal active centers significantly improves the relative capacity, and the fluffy and porous morphology also facilitates the insertion and extraction of lithium ions.
[0054] The humic acid-based metal coordination materials prepared in Examples 1-2, the manganese metal-organic framework material prepared in Comparative Example 1, and pure humic acid in Comparative Example 2 were subjected to rate performance tests at different current densities. The voltage range was 0–3 V, and the test temperature was 30 °C. The resulting rate performance graphs are shown below. Figure 8 As shown. By Figure 8It can be seen that, compared with the manganese metal-organic framework material prepared in Comparative Example 1 and the pure humic acid in Comparative Example 2, the HA-Mn material in Example 1 and the HA-Co material in Example 2 both showed good stability at various current densities, demonstrating excellent rate performance and good electrochemical reversibility.
[0055] In summary, the humic acid-based metal coordination material prepared by this invention effectively improves the poor cycle stability and rate performance of the HA electrode, while providing considerable specific capacity. Compared with commercial graphite anodes, the humic acid-based metal coordination material prepared by this invention also has certain advantages in terms of rate performance and specific capacity.
[0056] In the above-described cyclic voltammetry, AC impedance, and constant current charge-discharge tests, the humic acid-based metal coordination material prepared in the above examples, the Mn-MOFs material prepared in Comparative Example 1, and the pure humic acid prepared in Comparative Example 2 were used as active materials to prepare working electrodes. These were assembled into CR2032 coin cells in an argon glove box. The coin cells were tested on an electrochemical workstation and a Blue Battery testing system. In the coin cells: the electrolyte was a commercially available 1M LiPF6 in EC+DEC (1:1, vol%) electrolyte; the counter electrode was a 1mm thick lithium metal sheet; and the separator was a Celgard 2325 separator.
Claims
1. A method for preparing a humic acid-based metal coordination material, characterized in that... Includes the following steps: S1. Mix the aqueous solution of metal salt and the aqueous solution of humic acid evenly to obtain a mixed solution, wherein the metal salt is selected from at least one of water-soluble manganese salt and cobalt salt; The manganese salt is selected from at least one of manganese chloride, manganese sulfate, and manganese nitrate, and the cobalt salt is selected from at least one of cobalt chloride, cobalt sulfate, and cobalt nitrate; S2. The mixed solution is subjected to a hydrothermal reaction at a temperature of 120~190℃ for 12~24 h. After the reaction is completed, the mixture is centrifuged, washed, and the resulting precipitate is dried to obtain the humic acid-based metal coordination material with a fluffy and porous snowball-like structure.
2. The method for preparing humic acid-based metal coordination materials according to claim 1, characterized in that: The mass concentration of the metal salt aqueous solution is 1-10%, and the mass concentration of the humic acid aqueous solution is 0.1-1%.
3. The method for preparing humic acid-based metal coordination materials according to claim 1, characterized in that: The mass ratio of the metal salt to humic acid is 1~10:
1.
4. The application of a humic acid-based metal coordination material prepared by any one of claims 1-3 in a lithium-ion battery.
5. The application of the humic acid-based metal coordination material according to claim 4, characterized in that: The humic acid-based metal coordination material is used as an active material for preparing the negative electrode of a lithium-ion battery.